1994
DOI: 10.1139/z94-279
|View full text |Cite
|
Sign up to set email alerts
|

Influence of reduced food availability on growth of captive American kestrels

Abstract: Captive American kestrels (Falco sparverius) were used to model the effect of low prey availability on growth and survivorship potential in nestling raptors. The experimental design consisted of 4 treatments: nestlings were fed ad libitum (100% diet) or on increasingly restricted diets (90, 80, and 70% of the ad libitum diet). Nestlings fed a reduced diet grew significantly more slowly than those fed the ad libitum diet, as shown by the body mass growth constant. The restricted diet had no significant effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 24 publications
6
26
0
Order By: Relevance
“…In both our control and food-restricted house sparrows, we observed rapid increases in tarsus length during the first week post-hatch, followed by slowed growth to day 12. Growth of the tarsus, skull and wing of food-restricted house sparrows was maintained in line with that of adequately fed controls, which is in agreement with previous studies showing prioritization of skeletal growth (relative to mass gain) in altricial young faced with acute or chronic, moderate restriction (Negro et al, 1994;Lacombe et al, 1994;Lepczyk and Karasov, 2000;Moe et al, 2004). An equivalent prioritization of skeletal growth was observed in our preliminary study of 25% chronic restriction lasting until 25days post-hatch in house sparrows (Killpack et al, 2010).…”
Section: T L Killpack and W H Karasovsupporting
confidence: 90%
See 1 more Smart Citation
“…In both our control and food-restricted house sparrows, we observed rapid increases in tarsus length during the first week post-hatch, followed by slowed growth to day 12. Growth of the tarsus, skull and wing of food-restricted house sparrows was maintained in line with that of adequately fed controls, which is in agreement with previous studies showing prioritization of skeletal growth (relative to mass gain) in altricial young faced with acute or chronic, moderate restriction (Negro et al, 1994;Lacombe et al, 1994;Lepczyk and Karasov, 2000;Moe et al, 2004). An equivalent prioritization of skeletal growth was observed in our preliminary study of 25% chronic restriction lasting until 25days post-hatch in house sparrows (Killpack et al, 2010).…”
Section: T L Killpack and W H Karasovsupporting
confidence: 90%
“…However, food-restricted birds maintained skeletal growth in line with controls and fledged at the same age (Killpack et al, 2010). This pattern of reduced asymptotic body mass and maintenance of skeletal growth and fledging date has also been demonstrated with chronic 20-30% food restriction in captive American kestrels (Lacombe et al, 1994). Thus, maintenance of skeletal growth within the limitations imposed by chronic, moderate food restriction may allow birds to avoid the enduring negative consequences of reduced structural size on competitive abilities and survival within and outside of the nest.…”
Section: T L Killpack and W H Karasovmentioning
confidence: 58%
“…Our findings of reduced body mass, organ mass, and structural size in food-restricted nestlings support the previously demonstrated resource dependence of growth and maintenance in young birds (Lacombe et al 1994;Negro et al 1994;Burness et al 2000;Brzęk and Konarzewski 2001;Dahdul and Horn 2003;Moe et al 2004;Killpack and Karasov 2012a). Body mass, Food Restriction and Immune Development in Nestlings 203 organ mass, and structural size were recovered in refed birds, indicating flexibility to immediate resource supply.…”
Section: Comparison With Patterns Of Growth and Development During Resupporting
confidence: 90%
“…Growth rates of altricial nestlings can be flexible to resource supply, and in some cases nestlings have been shown to slow growth during periods of food restriction and later "catch up" following return to adequate resources (Lepczyk and Karasov 2000;Bize et al 2006;Hegyi and Török 2007;Criscuolo et al 2008Criscuolo et al , 2011Killpack et al 2014). It is well documented that allocation patterns to organ growth and maintenance metabolism are altered during food restriction in nestlings (Lacombe et al 1994;Negro et al 1994;Burness et al 2000;Brzęk and Konarzewski 2001;Dahdul and Horn 2003;Moe et al 2004;Killpack and Karasov 2012a). Recent studies have shown that components of both the innate (e.g., antimicrobial proteins, natural antibodies, complement) and adaptive (e.g., B-and Tlymphocyte activities) arms of the immune system rapidly increase throughout the nestling and postfledging period of altricial birds (Palacios et al 2009;Stambaugh et al 2011;Killpack and Karasov 2012b;Killpack et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation